Engine Performance Testing and Fuel Consumption of Unmanned Aerial Vehicle with Octane Rating Variations - Kusumoaji, Danartomo; Hartono, Hartono; Rohman, Abdul; Yunus, Meila Filhasni (Computational And Experimental Research In Materials And Renewable Energy, 2023)
Unmanned aerial vehicles or often known as Drone / UAV are used for various missions, some of which are for aerial photography, monitoring, load testing, spraying fertilizers and so on. The performance of unmanned aircraft is supported by several aspects, one of which is the propulsion or engine of the aircraft. The Aeronautical Technology Research Center, BRIN, Indonesia has several series of unmanned aerial vehicles used for several missions. To support the missions that must be taken by unmanned aircraft, engine performance is one of the important factors for carrying out missions. In this study, engine testing will be carried out to see the performance of the engine by varying the octane rating of the fuel used. This test used an LSU-04 aircraft engine with a 3W-110i B2 engine type with a capacity of 110 cc and a propeller size of 26x8. Engine tests were carried out using 3 types of fuel with octane ratings of 92, 95 and 98. The data taken is engine speed data (rpm), thrust data and fuel consumption data. Tests and measurements were carried out at the highest rpm value of 6000 rpm and the test was carried out for 1 hour. From the test results, the results were obtained that the performance of the engine that has the largest thrust value is the one that uses fuel with an octane rating of 92, namely with a thrust value of 14.13 kgf, while the thrust value for fuel with an octane rating of 95 is 13.35 kgf, and the thrust produced in fuel with an octane rating of 98 is 13.06 kgf. Then from the results of measuring fuel consumption, the most economical value is an engine that uses fuel with an octane rating of 98, which consumes 1007 ml of fuel, while for fuel consumption with an octane value of 95 of 1028 ml and for an octane value of 92 of 1061 ml.Keywords: UAV, 3W-110i B2 Engine, 92 Octane, 95 Octane, 98 Octane, Engine Performance